Silver oxide nanoparticles-decorated tantala nanotubes for enhanced antibacterial activity and osseointegration of Ti6Al4V - Sarraf, Masoud; Dabbagh, Ali; Bushroa, Abdul Razak; Nasiri-Tabrizi, Bahman; Hosseini, Hamid Reza Madaah; Saber-Samandari, Saeed; Abu Kasim, Noor Hayaty; Lum, Kah Yean; Sukiman, Nazatul Liana (Elsevier, 2018)
A long-term antibacterial activity of implants without compromising their biocompatibility is highly desirable to minimize the biomaterial-associated infections. Although tantalum oxide nanotubes (Ta2O5 NTs) are promising coating materials for orthodontics and orthopedics applications, their insufficient antibacterial activity retains vulnerability to post-implantation infections. This study aimed to endow antibacterial characteristics to the Ta2O5 NTs-coated Ti6Al4V substrates by decoration of silver oxide nanoparticles (Ag2O NPs). The well-adherent Ta2O5 NTs were grown via anodization of a pure tantalum (Ta) layer coated by physical vapor deposition (PVD) on the Ti6Al4V substrates. The Ag2O NPs were then decorated on the edges and walls of nanotubes through a secondary PVD under controlled conditions. The silver oxide nanoparticles-decorated tantala nanotubes (Ag2O NPs-decorated Ta2O5 NTs) promoted the formation of bone-like apatite layer and significantly reduced the viability of Escherichia coli (E. coli) cells. The prepared coating also increased the density and spreading of osteoblast cells in comparison to bare substrate. These results suggest that decorating the Ta2O5 NTs with Ag2O nanoparticles could improve antibacterial activity and the osseointegration of Ti6Al4V implants.